Cyber Security Challenges in Social Media : Bridging Awareness and Action - Uttamsagar, K. (Indian Journal of Computer Science, 2025)
The use of social media as a primary tool for communication and information sharing has posed severe cyber security threats. This has exposed users to vogue threats like identity phishing, frauds, and data hijacking among others, amplified by poor security cultures and conscientization. The present paper aims at discussing the theoretical framework of cyber security when it comes to social media, understanding user behavior, and assessing risks that are inherent to the platform. An organized survey of 200 respondents gives essential information on user awareness, practices, and encounters with cyber dangers. The results uncover basic gaps in client information and the application of defensive measures. This considers emphasizes the critical requirement focused on mindfulness campaigns, user-friendly security highlights, and stage responsibility. The discoveries contribute to upgrading the advanced ecosystem’s security and recommend techniques for relieving dangers. The suggestions highlight collaborative endeavors among clients, designers, and policymakers to cultivate a culture of cyber security awareness.